Determinants of innovation activities and SME absorption – Case study of Germany - Prokop, Viktor; Stejskal, Jan (Univerzita Pardubice, 2019)
SME’s are integral pillars in ladder of innovation. Due to their proximity to end users and their flexibility, they are credited with the creation of ground level product and process innovations in their local and world markets. SMEs absorption of innovations is significantly assisted by the entrepreneurial environment, globalization tendencies, rapidly changing technological issues of the environment as well as other determinants. However, depending on the industry, determinants of innovation affects each firm differently depending on the type of innovation considered. The goal of this research is therefore, to analyse what determinants influence the innovation activities of small and medium enterprises across three different German industries, namely, in the Electrical, Chemical and Pharmaceutical and the Metal Industry. Results from the SMEs were compared against themselves as well as SMEs from the three considered industries. This paper used data from the Community Innovation Survey (2010-2012) which employed stratified sampling technique with surveys. Logistic regression tool was used to analyse the impact of certain activities and expenditures, information and competitive strategies on product on process innovation. The research eventually discovered that the determinants influencing product and process innovations in selected enterprises varied according to the size of enterprise analysed. It was proposed that small enterprises should primarily focus on In-house R&D and acquisition of capital assets whilst medium size enterprises would be best served in concentrating on training for innovative activities.
Keywords: innovation activities; determinant; innovation capacity; Germany; O38; O47; H50; C33